Review paperTrophoallergens in the aetiopathogenesis of atopic dermatitis - Rosińska, Anna; Stajkowska, Iwona; Cichy, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Atopic dermatitis (AD) is a chronic, inflammatory disease, affecting the epidermis and the dermis. AD is a very common disease – it is recognized to affect 5% of children. Trophoallergens, particularly in children, seem to play a key role in the aetiopathogenesis of AD. Sensitization to food allergens seems to be a triggering factor for the so-called allergic march phenomenon – from food allergy to AD and then to asthma. Clinical outcome of the disease depends on the immunological system, the age of the child, and whether it was breast-fed or not. Due to the immaturity of the immune and digestive system in infants, breast-feeding up to 4-6 months and avoiding solid food until the 6th month of life are optimal. Recently, a lot of attention has been paid to the possible role of probiotics in the treatment and prevention of inflammatory diseases of intestines and skin.